Expectations of and perceived need for civil war in the USA: findings from a 2023 nationally representative survey - Garen J. Wintemute; Yueju Li; Bradley Velasquez; Andrew Crawford; Paul M. Reeping; Elizabeth A. Tomsich (BMC, 2024)
Abstract Background Surveys have found concerningly high levels of agreement that the United States will experience civil war soon. This study assesses variation in expectation of and perceived need for civil war with respondent sociopolitical characteristics, beliefs, firearm ownership, and willingness to engage in political violence. Methods Findings are from Wave 2 of a nationally representative annual longitudinal survey of members of the Ipsos KnowledgePanel, conducted May 18-June 8, 2023. All respondents to 2022's Wave 1 who remained in KnowledgePanel were invited to participate. Outcomes are expressed as weighted proportions and adjusted prevalence differences, with p-values adjusted for the false discovery rate and reported as q-values. Results The completion rate was 84.2%; there were 9385 respondents. After weighting, half the sample was female (50.7%, 95% CI 49.4%, 52.1%); the weighted mean (± standard deviation) age was 48.5 (25.9) years. Approximately 1 respondent in 20 (5.7%, 95% CI 5.1%, 6.4%) agreed strongly or very strongly that "in the next few years, there will be civil war in the United States." About 1 in 25 (3.8%, 95% CI 3.2%, 4.4%), and nearly 40% (38.4%, 95% CI 32.3%, 44.5%) of those who strongly or very strongly agreed that civil war was coming, also agreed strongly or very strongly that "the United States needs a civil war to set things right." Expectation of and perceived need for civil war were higher among subsets of respondents who in Wave 1 were more willing than others to commit political violence, including MAGA Republicans, persons in strong agreement with racist beliefs or statements of the potential need for violence to effect social change, persons who strongly approved of specified extreme right-wing political organizations and movements, firearm owners who purchased firearms in 2020 or later, and firearm owners who carried firearms in public all or nearly all the time. Conclusions In 2023, the expectation that civil war was likely and the belief that it was needed were uncommon but were higher among subsets of the population that had previously been associated with greater willingness to commit political violence. These findings can help guide prevention efforts.